Synthesis and characterization of zinc oxide nanorods sensitised by Bi₂S₃, Ag₂S and Ag₂S-Bi₂S₃ for photoelectrochemical application - Abdullah M., Alzahrani Asla (2020)
This study focuses on the synthesis and characterisation of zinc oxide nanorods sensitised by narrow bandgap energy metal chalcogenides for photoelectrochemical application. Zinc oxide (ZnO) is a promising oxide semiconductor for photoelectrochemical application. Although it is very efficient in absorbing UV light, its wide bandgap is not ideal for visible light absorption. To solve this problem, heterostructures of the nanocomposite semiconductors such as bismuth sulfide/zinc oxide (Bi2S3/ZnO), silver sulfide/zinc oxide (Ag2S/ZnO) and bismuth sulfide /silver sulfide/ zinc oxide (Bi2S3/Ag2S/ZnO), are proposed to be the alternative conversion medium, as they could possibly harvest larger spectrum of sunlight. There are a variety of modification methods can be applied during the synthesis in order to increase the overall photoconversion efficiency of these nanocomposites such as deposition of sensitised narrow band gap energy materials on the surface of ZnO nanorod arrays. The deposition is expected to result in the modification of the electronic interface and facilitating charge carrier transfer between the coated material and the host semiconductor. In this study, ZnO nanoparticles seed layer (NPs) was prepared by sol- gel spin coating technique followed by heat-treatment at different temperatures to optimise the nucleation. ZnO nanorod arrays (NRAs) were then grown through a simple, facile hydrothermal method. The effect of hydrothermal growth temperature and duration were optimised to ensure achieving the high aspect ratio of ZnO NRAs. Bi2S3/ZnO NRAs/ITO, Ag2S/ZnO NRAs/ITO were prepared using successive ionic layer adsorption and reaction (SILAR) method. In addition, considering the effect of various parameters on formation of Bi2S3/ZnO NRAs and Ag2S/ZnO NRAs nanocomposite, the synthesis was carried out with variation of SILAR cycles number, dipping time, concentration of cationic precursor, pH, and annealing temperature. The formation of ZnO nanorods and Bi2S3 was noticed when the colour of the samples changed from colourless to white for ZnO, and dark brown for Bi2S3/ZnO. The powder X-ray diffraction (XRD) analysis verified that the synthesised ZnO NRAs sample has hexagonal phase while Bi2S3 has an orthorhombic crystal structure. The deposited photosensitiser has no effect on the host material structure. The small nanoparticles of Bi2S3 on ZnO NRAs was observed by field emission scanning electron microscopy (FE-SEM). The red shifted absorbance spectra of the UV-visible spectrophotometry were observed after depositing Bi2S3 on ZnO NRAs. On the other hand, the transmission electron microscopy (TEM) provided the estimated average particle size of the Bi2S3 /ZnO nanoparticles heterostructure followed by determination of lattice fringe (d-spacing) from high-resolution transmission electron microscopy (HR-TEM). Bi2S3/ZnO NRAs nanocomposite synthesised at optimum condition gave a maximum photocurrent density of 2.76 mA/cm2 and photoconversion efficiency of 3.17% which was 13 times greater than the plain ZnO NRAs (0.25%). The combination of wide bandgap energy (ZnO) with narrow bandgap energy semiconductor caused bending of different Fermi-level positions. Thus, the photogenerated electrons can be transferred easily from conduction band of Bi2S3 to the conduction band of ZnO while the holes transferred from the valance band of ZnO NRAs to the valance band of Bi2S3. Furthermore, the formation of ZnO nanorods and Ag2S was observed as the colour of the samples changed from colourless to white for ZnO NRAs and dark brownish colour for the Ag2S/ZnO sample. XRD, FE-SEM and UV-visible spectrophotometry analyses showed that the samples synthesised had a monoclinic phase, red shifted on the absorption edge of Ag2S/ZnO NRAs/ITO. Additionally, ternary nanocomposite thin film Bi2S3/Ag2S/ZnO NRAs has been optimised via controlling SILAR cycle number, dipping time, and annealing temperature. Results showed that due to its narrow bandgap, Bi2S3 and Ag2S deposited samples were able to harvest more light compared to plain ZnO NRAs. In comparison with ZnO NRAs/ITO PEC electrode with a bandgap of 3.22 eV, Bi2S3/ZnO /ITO and Ag2S/ZnO/ITO showed much smaller bandgaps of 1.95 eV, 1.78 eV, respectively. This cascading bands gap alignment decreased the chance for electron-hole recombination and enhanced the efficiency of electrons collection. The photoelectrochemical performance of the bare ZnO nanorods, Bi2S3/ZnO, Ag2S/ZnO was examined under the illumination of a simulated visible light. The enhancement of photoconversion efficiency was observed to be 3.17% for Bi2S3/ZnO, 2.33% for Ag2S/ZnO and 12.63% for Bi2S3/Ag2S /ZnO compared to plain ZnO nanorods sample of only 0.25%.